Tax policy under martial law - Anna Halaburda; Svitlana Shevchenko (Економічний вісник університету, 2022)
Relevance of the research topic. Tax policy is an integral part of the financial policy of the state. Taxes are the basis of the financial stability of the state and the guarantee of a competitive position in the world environment, the stimulation of economic activity and the implementation of social policy. The full-scale invasion of the Russian Federation on the territory of our state set the Government the task of revising previously chosen goals and reorienting them to ensure the country's defense capability and social security of citizens. In the conditions of martial law, it is important to ensure the implementation of the revenue part of the budget in order for the state to implement its functions. Formulation of the problem. The relevance of the chosen research topic is due to the importance of a detailed scientific analysis of tax policy under martial law, tax policy instruments and assessment of the state of the tax system. Analysis of recent research and publications. The issue of the theoretical and methodological foundations of tax policy and its role in the conditions of economic transformations is being studied by many domestic scientists, including: I. Chugunov [1], V. Andrushchenko [2], Z. Varnalii [3], O. Desyatniuk [4], T. Yefimenko [5], Yu. Ivanov [6], A. Krysovaty [7], L. Kozarezenko [8], M. Pasichny [9], A. Sokolovska [10], and others. Selection of unexplored parts of the general problem. Given the relevance of the research topic, the tax policy in the conditions of martial law requires in-depth research in order to identify problems and study the main ways of adapting the state's economy in conditions of war. Problem setting, research goals. The subject of the article's research is the theoretical and methodological foundations of tax policy. The purpose of the study is to reveal the essence of tax policy and methods of its implementation under martial law. Method and methodology of the study. In the process of studying the research questions, general scientific and special methods were used: systemic, structural, comparison, qualitative and quantitative analysis, scientific abstraction and synthesis. Field of application of results. The obtained research results should be used in conducting further scientific research on tax policy, the functioning mechanism of the tax system and its tools under martial law. Conclusions. The essence of tax policy under martial law is revealed. Changes to legislation and the tax mechanism, which were adopted since the introduction of martial law, were analyzed. Sources of tax revenues of the State Budget were determined and their level compared to the same period last year was assessed. The forecast and state of further development of the state's economy are analyzed.